논 생태계 내 둠벙의 저서성 대형무척추동물 군집구조 특성 - 최락중; Lak Jung Choe; 한민수; Min Su Han; 김미란; Miran Kim; 조광진; Kwang Jin Cho; 강기경; Kee Kyung Kang; 나영은; Yong Eun Na; et al. (Hanguk hwangyeong nonghak hoeji, 2013)
일반적으로 둠벙은 논 생태계 내 생물다양성 증진에 중요 한 역할을 하는 것으로 알려져 있지만, 농업생산성 증대를 위한 경지정리, 배수개선사업 등 농업환경 개선사업에 의하여 급격히 감소되었다. 근래에 들어 사회적으로 친환경농업의 활성화와 생물다양성에 대한 관심의 증대로 인하여, 논 생태계 내에 둠벙을 새롭게 복원하려고 하는 노력들이 시도되고 있는 실정이다. 본 연구에서는 둠벙의 저서성 대형무척추동물 군집 특성을 규명하고, 둠벙의 특성 및 입지조건과 저서성 대형무척추동물 군집의 관계를 분석하여 둠벙 복원의 기초자료를 제공하고자 하였다. 2010년부터 2012년까지 여덟 개 지역에서 15개의 둠벙을 대상으로 저서성 대형무척추동물에 대한 조사를 실시하였다. 조사결과 둠벙에서는 총 131종의 저서성 대형무척추동물이 서식하는 것으로 확인되어, 둠벙이 농업생태계 내 생물다양성의 유지 및 보전에 중요한 기능을 하는 것을 확인할 수 있었다. 저서성 대형무척추동물의 군집조성과 둠벙의 환경적 특성 및 입지조건의 분석에서는 입지적 특성이 둠벙의 저서성 대형무척추동물 군집조성에 가장 큰 영향을 미치는 요인으로 확인되었다. 특히 둠벙 둑의 형태 및 둠 벙 조성 후 경과시간도 군집조성에 영향을 미치는 것으로 나타나 둠벙의 입지적 특성과 함께 둠벙 복원시 고려되어야 할 사항으로 판단된다. BACKGROUND: Ecological functions of irrigation ponds were well known fact that important for biodiversity conservation in agricultural ecosystems. However, many irrigation ponds were destructed with changes of agricultural environment. The objective of this study is to appreciate the importance of ecological functions of irrigation pond. Furthermore, it presented to useful information for restorations of irrigation pond from analyses of correlations between benthic macroinvertebrate communities and locational factors of irrigation ponds. METHODS AND RESULTS: Benthic macroinvertebrate sampling was conducted from 2010 to 2012 at 15 study ponds. Comparisons of benthic macroinvertebrates diversity approached species richness and density, and statistical analyses were performed using independent t-test. A total of 131 species / 137,118 individuals of benthic macroinvertebrates were recorded during study period. Dominant taxa of benthic macroinvertebrates included Coleoptera, Hemiptera, and Odonata. Generally, benthic macroinvertebrate diversity in mountain region and existing ponds were showed higher than open field and created ponds, respectively. DCA ordination showed that benthic macroinvertebrate community was most correlated with locational characteristics of irrigation pond, and it correlated with bank type and age of pond. CONCLUSION(S): In conclusions, in order to restore ecological irrigation pond, it is necessary to consider environmental factors such as locational characteristics and bank types.